A Formation Reconfiguration Method for Multiple Unmanned Surface Vehicles Executing Target Interception Missions. (November 2020) - Fan, Jiajia; Li, Ye; Liao, Yulei; Ma, Teng; Ge, Yu; Wang, Zixiao
Abstract: This paper presents a formation reconfiguration method for multiple unmanned surface vehicles (MUSVs) executing target interception missions. In its essence, the objective can be described as follows: given a target at a given position and a set of USVs, maneuver the USVs from their initial positions towards the target so that they end forming a "protective barrier" in the vicinity of the target. In its simplest form, this barrier can be simply obtained through a colinear formation of the USVs, with the center at an appropriate distance from the target. This can be done in two distinct phases: maneuver planning and vehicle task assignment. In terms of maneuver planning, an adaptive null-space-based (ANSB) strategy is adopted. In order to address explicitly the maneuverability constraints of each vehicle (for example, intrinsic limitations on the rate of turn while progressing at a given linear speed), an improved adaptive null space method (IMANSB) is proposed for vehicle speed assignment. In terms of task assignment, by introducing the virtual attractive force and rigid body dynamics, a method of redefined Dubins path was proposed, which can more quickly match the optimal path that conforms to the heading angle of the departure and the heading angle of the destination. And, a method of formation reconfiguration for sea surface target interception of USV was presented, including spatial decoupling search and redefined Dubins path planning, in order to solve the problem of multi-objective optimization of the MUSV formation internal reconfiguration which is helpful to accelerate formation forming by considering the influence of cooperative time consistency and total distance. To verify the feasibility of proposed method, a simulation platform for the formation control of MUSVs was established, and a simulation experiment was conducted.